2015
DOI: 10.1016/j.watres.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Tracking changes in the optical properties and molecular composition of dissolved organic matter during drinking water production

Abstract: Absorbance, 3D fluorescence and ultrahigh resolution electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI-FT-ICR-MS) were used to explain patterns in the removal of chromophoric and fluorescent dissolved organic matter (CDOM and FDOM) at the molecular level during drinking water production at four large drinking water treatment plants in Sweden. When dissolved organic carbon (DOC) removal was low, shifts in the dissolved organic matter (DOM) composition could not be detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
114
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(133 citation statements)
references
References 55 publications
18
114
1
Order By: Relevance
“…Accordingly, studies using other methods than mass spectrometry also found that compounds with low H/C such as polyphenols and aromatics are preferentially adsorbed (Kaiser, ; Kaiser et al, ; Kalbitz et al, ; Kothawala et al, ). This is consistent with the use of coagulation (e.g., to metals) to remove aromatic, high molecular weight compounds during drinking water treatment (Lavonen et al, ; Matilainen et al, ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Accordingly, studies using other methods than mass spectrometry also found that compounds with low H/C such as polyphenols and aromatics are preferentially adsorbed (Kaiser, ; Kaiser et al, ; Kalbitz et al, ; Kothawala et al, ). This is consistent with the use of coagulation (e.g., to metals) to remove aromatic, high molecular weight compounds during drinking water treatment (Lavonen et al, ; Matilainen et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…2012). This is consistent with the use of coagulation (e.g., to metals) to remove aromatic, high molecular weight compounds during drinking water treatment (Lavonen et al, 2015;Matilainen et al, 2010).…”
Section: Selective Dom Adsorptionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, these conventional approaches are not able to elucidate the molecular compositions of DOM. Recently, non-targeted analysis through ultrahigh resolution mass spectrometry (MS) such as Fourier transform ion cyclotron mass spectrometry (FT-ICR MS) and Orbitrap mass spectrometry (Orbitrap MS) have been applied to analyze DOM in aquatic environments [11][12][13][14][15][16] as well as DOM in drinking water and wastewater effluent [17][18][19][20]. These instruments can resolve complex DOM extracted by solid-phase extraction (SPE) and assign molecular formula to each component based on accurate mass.…”
Section: Introductionmentioning
confidence: 99%
“…Increased desire to constrain the role of inland waters in global carbon budgets has shown that fluvial organic carbon (OC) levels do not remain static in the downstream fluvial continuum (Battin et al, ; Cole et al, ; Fasching, Behounek, Singer, & Battin, ; Ward et al, ). Additionally, the nature and mechanisms of downstream changes are also of interest to water suppliers, as many water collection areas particularly at mid‐to‐high northern latitudes (e.g., Lavonen et al, ; Ritson et al, ) contain substantial areas of peatland, commonly resulting in high concentrations of dissolved OC (DOC); the removal of which is a major water treatment cost (Worrall et al, ). Therefore, understanding the within‐catchment relationships between fluvial OC composition, concentration, and transformations is important for effective management of these environments.…”
Section: Introductionmentioning
confidence: 99%